Forming a Music Teacher's Conducting Skills - D. Raimova (Researchparks Publishing, 2021)
The article discusses the importance of preparing a music teacher for the development of professional qualities, such as choral management skills, good artistic taste, organizational and initiative abilities, independent creative thinking and work without deviations from the work process.